Toward sustainable and comprehensive control of schistosomiasis in China: lessons from Sichuan. - Edmund Y W Seto; Justin V Remais; Elizabeth J Carlton; Shuo Wang; Song Liang; Paul J Brindley; Dongchuan Qiu; Robert C Spear; Long-De Wang; Tian-Ping Wang; Hong-Gen Chen; Xing-Qi Dong; et al. (Public Library of Science (PLoS), 2011)
Triggered by a fascinating publication in the New England Journal of Medicine detailing China's new multi-pronged strategy to control and eventually interrupt the transmission of Schistosoma japonicum, this PLoS Neglected Tropical Diseases Debate critically examines the generalizability and financial costs of the studies presented from the marshlands of the lake region. Edmund Seto from the University of California and colleagues emphasize that the epidemiology and control of schistosomiasis varies according to the social-ecological context. They conjecture that the successful intervention packages piloted in the lake region is not fully fit for the hilly and mountainous environments in Sichuan and Yunnan provinces, and hence call for more flexible, setting-specific, and less expensive control strategies. In response, Xiao-Nong Zhou from the National Institute of Parasitic Diseases at the Chinese Center of Disease Control and Prevention and colleagues explain the steps from designing pilot studies to the articulation and implementation of a new national control strategy through a careful process of scaling-up and adaptations. Finally, the two opponents converge. The need for integrated, intersectoral, and setting-specific control measures is stressed, supported by rigorous surveillance and continuous research. Experiences and lessons from China are important for shaping the schistosomiasis elimination agenda.